KETAHANAN PANGAN RUMAH TANGGA TANI PERKOTAAN DAN PERDESAAAN KABUPATEN GUNUNGKIDUL - Dyah Ayu Widyanitha; Suhatmini Hardyastuti; Jangkung Handoyo Mulyo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2015)
This research is conducted (1) to analyze share offarm householdfood expenditure/or the urban and rural,(2) to analyze the level of urban and rural energy farm household, (3) to analyze the level of household food securityurban and rural farm, (4) to analyze desirable dietary pattern of urban and rural farm household, (5) to understand influencingfactor of score food security farm household. The primary method for this research use descriptive analysis,sampling is done by using simple random method with 25 urban and 25 rural farm household in Gun ungkidu I. The data was analyzed by independent sample t-test and multiplier regression analysis by Ordinary Least Square (OLS).The results showed that (1) the share offarm household food expenditure in urban areas is lower than the share of food expenditure offarm households in rural areas, (2) the adequacy offarm household energy in rural areas is higherthan the farm households in urban area, (3) urban households food secure 20%, vulnerable food 40%, less food 12%, food insecurity 28%, yet rural household food secure 16%, vulnerable food 48%, less food 4%, food insecurity 32%,(4) food pattern expectations farm households in urban areas are not higher than the expectation of food patterns in rural areas, (5) factors that positively affect the food security of farm households are farm household income andlocation (urban and rural).